Urban biodiversity, city-dwellers and conservation: how does an outdoor activity day affect the human-nature relationship? - Assaf Shwartz; Alix Cosquer; Alexandre Jaillon; Armony Piron; Romain Julliard; Richard Raymond; Laurent Simon; Anne-Caroline Prévot-Julliard (PLoS ONE, 2012)
Urban conservation education programs aim to increase knowledge and awareness towards biodiversity and to change attitudes and behaviour towards the environment. However, to date, few urban conservation education studies have evaluated to what extent these programs have managed to achieve their goals. In this study, we experimentally explored the influence of an urban conservation activity day on individual knowledge, awareness and actions towards biodiversity, in both the short and longer term.We organised three activity days in Paris (France), during which people were invited to participate in urban conservation efforts. Both quantitative (questionnaire) and qualitative (interviews) methods were employed to investigate the influence of this short urban nature experience on the relationships that city-dwellers develop with nearby biodiversity. We found a strong positive correlation between the levels of participation and an immediate interest towards local urban biodiversity. In the longer term, however, although participants claimed to have gained more knowledge, local awareness and interest for species in their daily environment, they did not seem to extend this interest to participating in other related activities. These results highlight the complexity of validating the effectiveness of this type of education program for achieving conservation goals. Although such a short activity may only have a limited environmental impact, it nevertheless seems to increase people's knowledge, awareness, interest and concern. We therefore believe that when repeated locally, these short conservation education programs could enhance people's experience with nature in cities and achieve conservation goals more fully.